Sex differences in central nervous system plasticity and pain in experimental autoimmune encephalomyelitis. Issue 5 (May 2019) - Catuneanu, Ana; Paylor, John W.; Winship, Ian; Colbourne, Fred; Kerr, Bradley J.
Abstract : Abstract: Multiple sclerosis (MS) is a neurodegenerative autoimmune disease with many known structural and functional changes in the central nervous system. A well-recognized, but poorly understood, complication of MS is chronic pain. Little is known regarding the influence of sex on the development and maintenance of MS-related pain. This is important to consider, as MS is a predominantly female disease. Using the experimental autoimmune encephalomyelitis (EAE) mouse model of MS, we demonstrate sex differences in measures of spinal cord inflammation and plasticity that accompany tactile hypersensitivity. Although we observed substantial inflammatory activity in both sexes, only male EAE mice exhibit robust staining of axonal injury markers and increased dendritic arborisation in morphology of deep dorsal horn neurons. We propose that tactile hypersensitivity in female EAE mice may be more immune-driven, whereas pain in male mice with EAE may rely more heavily on neurodegenerative and plasticity-related mechanisms. Morphological and inflammatory differences in the spinal cord associated with pain early in EAE progression supports the idea of differentially regulated pain pathways between the sexes. Results from this study may indicate future sex-specific targets that are worth investigating for their functional role in pain circuitry. Abstract : Male mice with experimental autoimmune encephalomyelitis exhibit more robust staining of axonal injury markers and increased dendritic arborisation of deep dorsal horn neurons compared with females.